Generalized quasiperiodic epileptiform activity in sleep is associated with cognitive impairment in children with drug‐resistant focal lesional epilepsy. (15th October 2019) - Novak, Vilem; Maulisova, Alice; Jezdik, Petr; Benova, Barbora; Belohlavkova, Anezka; Liby, Petr; Tichy, Michal; Krsek, Pavel
Abstract: Objective: To evaluate the impact of generalized quasiperiodic epileptiform discharges ("hurdles") observed in non–rapid eye movement (NREM) sleep on cognitive function in children with intractable focal epilepsy. "Hurdles" pattern does not meet the criteria of the electrical status epilepticus in slow‐wave sleep (ESES). Methods: In a retrospective analysis, 24 patients with "hurdles" and their 24 peers matched for demographic and epilepsy‐related variables were compared in terms of neuropsychological domains and electroencephalography (EEG)–derived quantifiers. Both "hurdles" and controls were children between 2 and 19 years of age who had intractable focal epilepsy evaluated as candidates of resective epilepsy surgery. Results: Full‐scale intelligence quotient/developmental quotient (FSIQ/DQ) ( P  = .002) and visuoconstructional skills ( P  = .004) were significantly lower in children with "hurdles" compared to controls. Patients with "hurdles" presented with higher interictal spike indexes in sleep ( P  < .001, median difference −0.9, 95% confidence interval [CI] −1.4, −0.6) and wakefulness ( P  < .001, median difference −0.3, 95% CI −0.5, −1). Relative time of sleep spindles in NREM sleep was significantly reduced ( P  < .001, median difference 0.1, 95% CI 0.0, 0.1) in the "hurdles" group. The time proportion of sleep spindles represented a significant positive ( P  = .008) and spike index of generalized spikes in sleep a significant negative explanatory variable ( P  = .004) of FSIQ/DQ scores. The proportion of seizure‐free patients 2 years after epilepsy surgery did not differ significantly between the two groups ( P  = .19). Significance: Although the "hurdles" pattern does not fulfill the criteria of ESES, it is associated with a pronounced cognitive dysfunction. Disturbed sleep structure marked by reduced sleep spindles and generalized spiking in sleep is associated with worse cognitive performance. Despite having a generalized nature, we did not find a lower probability of postsurgical seizure freedom in patients with "hurdles" pattern.